Pilot Scale Study: First Demonstration of Hydrophobic Membranes for the Removal of Ammonia Molecules from Rendering Condensate Wastewater - Brian Brennan (12302813) (2020)
Hydrophobic membrane contactors represent a promising solution to the problem of recycling ammoniacal nitrogen (N-NH4) molecules from waste, water or wastewater resources. The process has been shown to work best with wastewater streams that present high N-NH4 concentrations, low buffering capacities and low total suspended solids. The removal of N-NH4 from rendering condensate, produced during heat treatment of waste animal tissue, was assessed in this research using a hydrophobic membrane contactor. This study investigates how the molecular composition of rendering condensate wastewater undergo changes in its chemistry in order to achieve suitability to be treated using hydrophobic membranes and form a suitable product. The main objective was to test the ammonia stripping technology using two types of hydrophobic membrane materials, polypropylene (PP) and polytetrafluoroethylene (PTFE) at pilot scale and carry out: (i) Process modification for NH3 molecule removal and (ii) product characterization from the process. The results demonstrate that PP membranes are not compatible with the condensate waste as it caused wetting. The PTFE membranes showed potential and had a longer lifetime than the PP membranes and removed up to 64% of NH3 molecules from the condensate waste. The product formed contained a 30% concentrated ammonium sulphate salt which has a potential application as a fertilizer. This is the first demonstration of hydrophobic membrane contactors for treatment of condensate wastewater. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms21113914